Brexit and Nostalgia. Issue 3 (4th May 2019) - Campanella, Edoardo; Dassù, Marta
Abstract : An infatuation with a distorted past deluded millions of British citizens and hundreds of pro-Brexit politicians about the future of their country outside Europe.